Circular_0086414 induces SPARC like 1 (SPARCL1) production to inhibit esophageal cancer cell proliferation, invasion and glycolysis and induce cell apoptosis by sponging miR-1290. Issue 5 (2nd May 2022) - Jiang, Qingfeng; Wang, Haoran; Yuan, Dongfeng; Qian, Xin; Ma, Xiaochao; Yan, Ming; Xing, Wenqun
ABSTRACT: Circular RNA (circRNA) plays an important role in cancer progression. Here, we investigated the function of circ_0086414 in the malignant progression of esophageal cancer (EC). RNA expression of circ_0086414, microRNA-1290 (miR-1290), and SPARC like 1 ( SPARCL1 ) was detected by quantitative real-time polymerase chain reaction. The protein levels of N-cadherin, E-cadherin, and SPARCL1 were checked by Western blotting analysis. Cell proliferation was investigated by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), 5-Ethynyl-29-deoxyuridine (EdU), and cell colony formation assays. Cell invasion and apoptosis were analyzed by transwell invasion assay and flow cytometry analysis, respectively. Glycolysis was evaluated by analyzing glucose consumption and lactate production. In an xenograft mouse model, the effect of circ_0086414 on tumor tumorigenesis was investigated. The interactions among circ_0086414, miR-1290, and SPARCL1 were identified by dual-luciferase reporter and RNA pull-down assays. Results showed that circ_0086414 and SPARCL1 expression were significantly downregulated, while miR-1290 was upregulated in EC tissues and cells. EC patients with low circ_0086414 expression had a poor prognosis. Increasing circ_0086414 expression led to decreased EC cell proliferation, invasion and glycolysis and increased cell apoptosis, accompanied by a decrease of N-cadherin expression and an increase of E-cadherin expression. Also, the enforced expression of circ_0086414 delayed tumor tumorigenesis. Besides, circ_0086414 acted as a miR-1290 sponge and regulated EC cell processes by binding to the miRNA. MiR-1290 also participated in EC malignant progression through SPARCL1 . Further, circ_0086414 stimulated SPARCL1 production by negatively regulating miR-1290. Thus, circ_0086414 inhibited EC cell malignancy through the miR-1290/ SPARCL1 pathway, providing a reliable target for the therapy of EC. Graphical Abstract: uf0001